Invasion of a Legume Ecosystem Engineer in a Cold Biome Alters Plant Biodiversity - Vetter, Vanessa M. S.; Tjaden, Nils B.; Jaeschke, Anja; Buhk, Constanze; Wahl, Veronika; Wasowicz, Pawel; Jentsch, Anke (Frontiers in Plant Science, 2018)
Plant ecosystem engineers are widely used to combat land degradation. However, the ability of those plants to modulate limiting abiotic and biotic resources of other species can cause damage to ecosystems in which they become invasive. Here, we use Lupinus nootkatensis as example to estimate and project the hazardous potential of nitrogen fixing herbaceous plants in a sub-polar oceanic climate. L. nootkatensis was introduced to Iceland in the 1940s to address erosion problems and foster reforestation, but subsequently became a high-latitude invader. In a local field survey, we quantified the impact of L. nootkatensis invasion at three different cover levels (0%, 10 – 50%, 51 – 100%) upon native plant diversity, richness and community composition of heath-, wood- and grasslands using a pairwise comparison design and comparisons of means. Afterwards, we scaled impacts up to the ecosystem and landscape level by relating occurrences of L. nootkatensis to environmental and human-mediated variables across Iceland using a species distribution model. Plant diversity was significantly deteriorated under high lupine cover levels of the heath- and woodland, but not in the grassland. Plant species richness of the most diverse habitat, the heathland, linearly decreased with lupine cover level. The abundance of small rosettes, cushion plants, orchids and small woody long-lived plants of the heath declined with invader presence, while the abundance of late successional species and widespread nitrophilous ruderals in wood- and grasslands increased. Distribution modelling revealed 13.3% of Iceland's land surface area to be suitable lupine habitat. Until 2061–2080, this area will more than double and expand significantly into the Central Highlands due to human mediation and increasingly favorable climatic conditions. Species-rich habitats showed a loss of plant species diversity and richness as well as a change in community composition even in low lupine cover classes. The future increase of suitable lupine habitat might lead to the displacement of cold-adapted native plant species and will certainly challenge conservation as well as restoration of ecosystems in the cold climate of Iceland, but also elsewhere. Lupine invasion speeds up succession, which may be additive with climate change effects, and accelerates ecological change in cold biomes.